Trust and politics in risk communication: Discourse analysis on radio frequency (RF) exposure in Malaysia - Fernandez, Prasana Rosaline; Kaur, Surinderpal; Lean, Mei Li; Ng, Kwan Hoong (Journal of Modern Languages, 2016)
Radio frequency (RF) exposure from the proliferation of telecommunication structures in Malaysia triggers concerns as growing numbers of people claim that RF emission is a health hazard. Effective risk communication is needed to address this misperception but most risk communication programmes fail because of public distrust. This is worrying as trust is a vital ingredient in communicating risk. As such, this study uses critical discourse studies and Candlin and Crichton’s focal theme of trust framework to examine how the politician’s discourse on RF exposure affects trust. The data is from four (4) face-to- face semi-structured interviews with politicians as they are answerable to their constituents’ protests. The findings reveal that politicians use blame avoidance and legitimization tactics to counter or reject the views of the ‘other’ in order to build trustworthy relationships with the local communities. But the politicians’ contradictory views on RF erode public trust and impede effective risk communication.